Efekivitas Role Model Guru Akidah Akhlak dalam Membentuk Karakter Disiplin Siswa - Luqman Hakim; Rohman Alif (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Teachers hold a key position in shaping the character of true Muslims. In the educational process, discipline is essential. However, student discipline at MTs Nurul Izzah Lumbangsari has been relatively low, as many students still violate school rules and regulations. Considering the importance of discipline, the researcher is encouraged to conducted a study entitled “The Effectiveness of Akidah Akhlak Teachers’ Role Modeling in Developing Students’ Disciplinary Character”. This study aims to identify the forms of exemplary behavior demonstrated by Akidah Akhlak teachers in fostering student discipline, as well as to examine the factors influencing the implementation of discipline among students. The research implements a qualitative field study approach, applying data collection techniques in forms of observation, interviews, and documentation. The data were then analyzed and validated through triangulation. The findings show that the exemplary behavior of Akidah Akhlak teachers plays a crucial role in fostering student discipline. Teachers consistently provide real-life examples in their daily activities at school. The implementation of student discipline is influenced by various supporting and inhibiting factors that are interconnected, forming a complex system. Overall, teacher exemplarity holds a central and most effective role in developing discipline. Consistent role modeling touches students’ hearts, leading them to view discipline not merely as an obligation, but as a reflection of responsibility, respect for time, and noble character.